IRRITABLE BOWEL SYNDROME (Homoeopathy for All, 2021)
Irritable bowel syndrome (IBS) is one of the most common functional gastrointestinal disorders. IBS is not the same as inflammatory bowel disease (IBD). It is not a disease but rather a disorder (abnormal function of the bowels) that results in a group  of symptoms. It is chronic, relapsing and often life-long, characterised by the presence of recurrent abdominal pain/discomfort associated with defaecation,  a change in bowel habit together with disordered defaecation that includes (constipation or diarrhoea or both), the sensation of abdominal distension,  and may include associated non-colonic symptoms. These morbidities may cause dehydration, lack of sleep, anxiety and lethargy which may lead to time off work,  avoidance of stressful or social situations and significant reduction in quality of life.
Keywords: Pulsatilla; Natrum carbonicum; abnormal function of the bowels